Impact Assessment Of Pharmaceutical Care Intervention On Newly Diagnosed Diabetes Mellitus Patients In A Tertiary Care Hospital Of A Sub Metropolitan City Of Western Nepal - Upadhyay, Dinesh Kumar (2013)
Poor socioeconomic status and lack of knowledge regarding disease are the major hurdles to be addressed in management of the disease. Therefore, a randomised control trial (RCT) study was conducted in five phases with the objectives of evaluating the impact of pharmaceutical care intervention on knowledge, attitude and practice (KAP), health-related quality of life (HRQoL), medication adherence and clinical outcomes, direct healthcare costs and satisfaction of newly diagnosed diabetes mellitus patients in a tertiary care hospital. A sample size of 162 patients was selected over 6-months duration (from July 2010 to December 2010) and randomization was done by 1:1:1 in three parallel groups: control group (n= 54), test 1 group (n= 54) and Test 2 group (n= 54). Interventions were carried out with the used of specially designed educational materials and tools. Descriptive and inferential statistics were performed in each part of the study. Appropriate non-parametric tests such as Kruskal-Wallis, Mann-Whitney U, Friedman and Wilcoxon signed rank tests (p≤0.05) have been used to find out the differences while Spearman order correlation test (p≤0.05) was used to find out the association among different dependent and independent variables. Patients’ age, monthly income, gender, education and occupation were significantly associated with their knowledge, attitude and practice scores about diabetes and its management.